Employment Protection, International Specialization, and innovation - Saint-Paul, Gilles (IMF Working Papers; Working Paper, 1996)
We develop a model to analyze the implications of firing costs on incentives for R and D and international specialization. The key idea is that, to avoid paying firing costs, the country with a rigid labor market will tend to produce relatively secure goods, at a late stage of their product life cycle. Under international trade, an international product cycle emerges where, roughly, new goods are first produced in the low firing cost country and then move to the high firing cost country. We show that in the closed economy, an increase in firing costs does not necessarily imply a reduction in R and D; it crucially depends on the riskiness of R and D activity relative to production activity. In the open economy, however, an increase in firing cost is much more likely to reduce R and D intensity.